PENGEMBANGAN BIOMAGAZINE TERINTEGRASI AUGMENTED REALITY (AR) PADA KONSEP GENETIKA DI SEKOLAH MENENGAH ATAS - Nurhidayah Nurhidayah; Suradi Tahmir; Hilda Karim (UNM Journal of Biological Education, 2018)
The type of the study is research and development (R&D) which aims to develop Biomagazine learning media integrated with Augmented Reality (AR) which is valid, practical, and effective in genetics concept. The stage of the research and development referred to Alessi & Trollip development model which consisted of 3 stages, namely (1) planning, (2) design, and (3) development. The instruments of the research consisted of three, namely (1) validity instrument in a form of validity assessment instrument of Biomagazine learning media integrated with AR and questionnaire validity assessment, (2) practicality instrument in a form of teachers and student’s responses questionnaire on Biomagazine learning media integrated with AR, and (3) effectiveness instrument in a form of learning result evaluation test. Based on the data analysis, it is obtained the average of media validity by two expert assessors by 4,31 for Biomagazine and 4,35 for the AR application. Both are in valid category. The practicality of the media obtained from the teachers’ responses is 93,33% (very strong) and the students’ responses is 86,66 (very strong). The effectiveness of the media is 90,00% of the students reach learning completeness score. The improvement of Biology learning results based on normalized gain is 0,71 (high category). Based on the results of the research, it can be concluded that Biomagazine learning media integrated with AR developed is valid, practical, and effective.